2014
DOI: 10.1016/j.biomaterials.2014.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of subcutaneous tissues surrounding long-term implants to oxygen

Abstract: Certain types of implanted medical devices depend on oxygen supplied from surrounding tissues for their function. However, there is a concern that the tissue associated with the foreign body response to implants may become impermeable to oxygen over the long term and render the implant nonfunctional. We report oxygen flux recordings from electrochemical oxygen sensor devices with wireless telemetry implanted in subcutaneous porcine tissues. The devices remained implanted for up to 13 weeks and were removed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…The value used here was based on in vivo measures of oxygen diffusion using phosphorescence quenching microscopy (32). Although this estimate is considerably lower than Krogh's original estimate (33), it is within two-to threefold of many current estimates from various tissues-particularly those using in vivo methods (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). The diffusion constant was adjusted for temperature to 38°C in our analysis of endotherms and to 25°C for ectotherms, based on a reported Q10 of 1.1 (47).…”
Section: Methodsmentioning
confidence: 93%
“…The value used here was based on in vivo measures of oxygen diffusion using phosphorescence quenching microscopy (32). Although this estimate is considerably lower than Krogh's original estimate (33), it is within two-to threefold of many current estimates from various tissues-particularly those using in vivo methods (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). The diffusion constant was adjusted for temperature to 38°C in our analysis of endotherms and to 25°C for ectotherms, based on a reported Q10 of 1.1 (47).…”
Section: Methodsmentioning
confidence: 93%
“…Such an increased affinity for oxygen is exacerbated by the decreased amount of oxygen present in wounded tissue. Gough et al have demonstrated that oxygen permeability within tissue surrounding an implant decreases over time before arriving at an asymptotic value, with the steepest drop coming in the first week [61,62]. Additionally, the concentration of unbound oxygen in tissue is much lower than that of glucose, meaning that oxygen limits the glucose oxidase reaction in the body [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…The oxygen concentration was adjusted using mass flow controllers (1179A, MKS Instruments, Inc., Andouver, MA, USA). Glucose challenges were performed by exposing the AnA hydrogels to varying physiologically relevant glucose concentrations (0–400 mg/dL in 10 mM TRIS with 10 mM CaCl 2 , 37 °C) at fixed oxygen concentrations (206.8 μM for ambient and 70 μM for interstitial oxygen concentration) [24]. The oxygen concentration was regulated by a vacuum degassing chamber (9000–1118, Systec) and vacuum pump (9000-1472, Systec).…”
Section: Methodsmentioning
confidence: 99%
“…These unique materials transduce chemical concentration into optical information (phosphorescence intensity or lifetime). While these materials were found to exhibit the desired response characteristics in benchtop testing, it was observed that the response often saturated at relatively low analyte concentrations when used in vivo; this undesired outcome has been attributed primarily to low tissue oxygen levels which have been found to be ≈3 times lower than air-equilibrated aqueous solutions [24,25]. These low oxygen concentrations disrupt the function of the bioresponsive material because they were designed and lab-proven based on a diffusion-reaction equilibrium expecting higher oxygen concentrations.…”
Section: Introductionmentioning
confidence: 99%